Motivasi belajar siswa: Menelisik peran relasi guru–siswa dan interaksi teman sebaya - Fitriyah, Ni’matul; Indawati, Ninik (SUKMA : Jurnal Penelitian Psikologi, 2024)
The purpose of carrying out this research is to: (1) analyze whether there is a simultaneous relationship between teacher-student relationships and peer interactions with learning motivation, (2) analyze whether there is a partial relationship between teacher-student relationships and peer interactions with learning motivation, and (3) analyze whether there is a partial relationship between teacher-student relationships and peer interactions with learning motivation. The population in this study was all students at SMP Negeri 1 Galis Pamekasan, totaling 375 students. Participants in the research were 150 students who were taken randomly without paying attention to the strata in the population. The research uses quantitative methods. Hypothesis testing uses the t-test for partial effects, and the F-test for simultaneous effects. Data analysis uses a multiple linear regression formula preceded by a classical assumption test. The research results show that (1) based on simultaneous analysis, there is a significant relationship between teacher-student relations and peer interactions with learning motivation. (2) the results of the partial analysis explain that there is a significant relationship between teacher-student relations and learning motivation, and (3) The results of the partial analysis explain that there is a significant relationship between peer interaction and learning motivation. In conclusion, there is a significant relationship between teacher–student relationships and peer interactions with learning motivation. Tujuan dari pelaksanaan penelitian ini untuk: (1) menganalisis apakah ada hubungan secara simultan antara relasi guru-siswa dan interaksi teman sebaya dengan motivasi belajar, (2) menganalisis apakah ada hubungan secara parsial antara relasi guru-siswa dan interaksi teman sebaya dengan motivasi belajar, dan (3) menganalisis apakah ada hubungan secara parsial antara relasi guru-siswa dan interaksi teman sebaya dengan motivasi belajar. Populasi dalam penelitian ini yaitu seluruh siswa SMP Negeri 1 Galis Pamekasan sejumlah 375 siswa. Partisipan dalam penelitian berjumlah 150 siswa yang diambil secara acak tanpa memperhatikan strata yang ada dalam populasi itu. Penelitian menggunakan metode kuantitatif. Uji hipotesis menggunakan uji-t untuk pengaruh parsial, dan uji-F untuk pengaruh simultan. Analisis data menggunakan rumus regresi linear berganda dengan didahului uji asumsi klasik. Hasil penelitian menunjukkan bahwa (1) berdasarkan analisis simultan ada hubungan yang signifikan antara relasi guru-siswa dan interaksi teman sebaya dengan motivasi belajar, (2) hasil analisis parsial menjelaskan ada hubungan yang signifikan relasi guru-siswa dengan motivasi belajar, dan (3) hasil analisis parsial menjelaskan ada hubungan yang signifikan interaksi teman sebaya dengan motivasi belajar. Kesimpulannya, ada hubungan yang signifikan antara relasi guru–siswa dan interaksi teman sebaya dengan motivasi belajar.